Peripheral Airway Obstruction in Association with Symptoms and Quality of Life in Asthma - Papapostolou G; Nasr A; Jarenbäck L; Romberg K; Tunsäter A; Ankerst J; Bjermer L; Tufvesson E (Journal of Asthma and Allergy)
Georgia Papapostolou,1 Abir Nasr,1 Linnea Jarenbäck,1 Kerstin Romberg,2 Alf Tunsäter,1 Jaro Ankerst,1 Leif Bjermer,1 Ellen Tufvesson1 1Department of Clinical Sciences, Lund, Respiratory Medicine, Allergology and Palliative Medicine, Lund University, Lund, Sweden; 2Health Care Centre, Näsets Läkargrupp, Höllviken, SwedenCorrespondence: Ellen Tufvesson, Department of Clinical Sciences, Lund, Respiratory medicine, allergology and palliative medicine, Lund University, Lund, BMC D12, 221 84 Lund, Sweden, Email ellen.tufvesson@med.lu.seIntroduction: Forced Oscillation Technique (FOT) is increasingly used to measure obstruction in the airways; however, the association between airway obstruction and the actual symptom burden in asthma is not known. Therefore, we aimed to investigate central and peripheral airway obstruction, measured by FOT, in association to symptoms and quality of life in asthma.Methods: 319 asthma patients were recruited and answered questionnaires focusing on symptoms (ACT, ACQ, Nijmegen, HADS and SNOT-22) and quality of life (MiniAQLQ and MiniRQLQ) and performed FOT measurements estimating airway resistance (R5: total resistance, R19: central resistance, R5-R19: peripheral resistance) and reactance (X5) during inspiration and expiration.Results: Asthma groups classified based on ACT score cut-off points at 16, 20, and 25 showed higher R5, R5-R19, and lower X5 with increasing symptoms, which was not evident when applying a cut-off of only 20. ACQ-5 cut-offs at 0.75 and 1.5 captured differences in R5 and X5, whereas a Nijmegen cut-off of 23 showed differences in R5 and R19. The total scores from most questionnaires (except for the HADS and SNOT-22) correlated with many of the FOT results, but there were different patterns of correlation between airway obstruction and symptoms in uncontrolled and controlled asthma. Additionally, specific questions were associated with airway obstruction.Conclusion: The increasing symptoms in patients with asthma assessed using questionnaires correlated well with predominantly increasing peripheral airway obstruction. A correlation also exists with the Nijmegen score, which is not specific to asthma. The cut-off points used to define asthma control may capture peripheral airway dysfunction.Keywords: asthma, symptom, quality of life, airway obstruction